324 Lumbar Interbody Fusion Status does not Correlate with Patient Reported Outcomes: Data Analysis from a Prospective Multi-center Study of Circumferential Lumbar Arthrodesis - Thaci, Bart; Ferry, Chris; Ventimiglia, Brieta; Glorioso, Tom; Martin, Kim; Martineck, Sarah; Panchal, Ripul R; Arnold, Paul M; Passias, Peter G; Moura, Alex De; Strenge, Brandon; Hill, Clint; et al. (Neurosurgery, 2017)
Abstract INTRODUCTION Circumferential lumbar arthrodesis leads to high fusion rates for degenerative lumbar spine. Interspinous posterior fixation pedicle screw fixation as an adjunct to interbody graft led to similar fusion rates and patient reported scores in prospective randomized multi-center study. Although commonly used as surrogates of each other it remains unclear whether the fusion scores correlate with patient reported outcomes. METHODS Data was collected as part of a prospective multi-center (11 investigators) study of 101 patients receiving single-level antero-lateral lumbar interbody fusion with supplemental interspinous process fixation (ISPF) or pedicle screw fixation (PSF) for the treatment of degenerative disc disease and/or spondylolisthesis. Subjects were randomized 2:1, ISPF to PSF, for posterior fixation. Patients were followed up to 24 months post-op. Patient reported outcome indices (ODI, SF-36) were collected at each follow-up time point. Lumbar x-ray radiographs were taken at 12 and 24 months. Interbody fusion was scored by an independent radiologist using the Brantigan-Stefee Fraser (BSF) criteria (BSF-1: pseudarthrosis; BSF-2: radiographic locked pseudarthrosis; BSF-3: radiographic fusion). A logistic regression model was used to determine whether a relationship existed between quality of fusion (BSF-3 vs. BSF-1&2) and clinical index improvement at 12 and 24 months. RESULTS >Change in ODI score at 12 and 24 months was not significantly associated with BSF score (P = 0.78 and P = 0.64, respectively). At 12 months,, BSF-3 patients had on average 1.4 greater reduction in ODI compared to BSF-1&2 (95% CI: -8.61, 11.41). Changes in SF-36 score were not significantly associated with BSF score (P = 0.63 and P = 0.18, respectively). For SF-36 Mental, BSF-3 patients had a 2.21 greater increase compared to BSF-1&2 (95% CI: -6.7, 11.13). Instead in SF-36 Physical, BSF-3 patients had a 4.14 lesser increase compared to BSF-1&2 (95% CI: -10.15, 1.88) CONCLUSION Radiological lumbar interbody fusion grading using BSF scale do not correlate with patient reported outcome.